Selected recommendations from international guidelines on obstructive sleep apnoea / Nurul Yaqeen Mohd Esa and Ahmad Izuanuddin Ismail. - Mohd Esa, Nurul Yaqeen; Ismail, Ahmad Izuanuddin (Universiti Teknologi MARA Cawangan Selangor, 2017)
Obstructive sleep apnoea (OSA) is increasingly seen as a major health threat globally. However, it is still underdiagnosed mainly among Asian population partly due to lack of understanding on the pathophysiology, and limited access to the diagnostic and management aspect of the disease. Recurring complete and/or partial collapses of the upper airways define OSA. Based on the number of apnoeas and/or hypopnoeas per hour of sleep, OSA is categorized as mild, moderate and severe. Both the American Association of Sleep Medicine (AASM) and American College of Physicians (ACP) has published guidelines regarding the management of OSA in adults. Three recommendations have been suggested by the guidelines which can be used to tailor the management of OSA. The aim of this article is to select relevant recommendations from these guidelines in epidemiology, pathophysiology, diagnostic procedures and treatment for proper management of OSA, while considering specific patient populations, such as hypertensive, diabetic, obese and Asian patients.